Ewolucja instrumentów prawnych ochrony wiarygodności dokumentów w systemie common law na przykładzie Irlandii zależnej i niepodległej - Jankowska-Prochot, Izabela (Czasopismo Prawno-Historyczne, 2018)
The aim of the analysis presented in the following article is to delineate the historical outline and the evolution of the criminal law regulations in the area of forgery of documents in Ireland under foreign rule and in independent Ireland. Special emphasis is placed on the implementation of English and later British legal solutions in Ireland as well as on their substantive similarities. A significant part of the deliberations is also devoted to modern regulations in the aforementioned area. Special attention is paid to the culpability (sometimes called the subjective element of a crime or Mens rea in Latin) and conduct (sometimes called the objective element of a crime or Actus reus in Latin) side of crime. Another discussed element is the punishment one is subjected to for committing the said offense. The study of the present issues is based on both the statutory interpretation of the previous and current regulations as well as on the doctrine and judicature. The assumed direct correlation to the structure of the article. The paper consists of an introduction, chapters devoted foreign rule and in independent Ireland as well as conclusions.